TINJAUAN YURIDIS KETENTUAN ABORSI PADA UNDANG – UNDANG NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DIKAITKAN DENGAN PERLINDUNGAN HAK ASASI MANUSIA - Putri, Annisya Rani; Edorita, Widia; ', Erdianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
Medically, abortion is to stop and expend pregnancy outcomes from the womb before the fetus can live beyond the content. Talk about abortion is closely related to the protection of Human Rights because a woman has the right to her body and herself and is entitled to live reproduction life safely, But on the other hand, the fetus in the womb is also entitled to live and thrive. These two things are indeed conflicting because it involves two lives. The purpose of writing this thesis, namely; First, the applicable provisions in the implementation of the provisions of abortion in Act No. 39 of 2009 About Health with Act No. 39 of 1999 About Human Rights; Second, the provision of abortion in Health Law is contrary to Human Rights.This type of research is classified in normative law research. Because in this study the authors conducted legal research literature. Source of data used are primary data, secondary data, and tertiary data, data collection techniques in this study using the method of assessment literature or documentary studies.From the research there are three main issues that can be inferred. First, Abortion in legal concepts relates to the values of morality that make abortion not merely contrary to the positive law of the state, but also against ethical and moral values, abortion may be made against women with medical indications. Secondly, although abortion is permissible for rape victims it is not justified to have an abortion because it has bypassed the highest constitution of our country. Therefore for the rape victim should duly protect the weaker soul (in case of no medical indication to the victim). Suggestion, Author, First, For the victims of rape is given understanding and advice that the fetus is in the womb is a gift from God Almighty, refused his gift, not grateful pleasure is an act that is disliked by Allah SWT and is a great sin, Second, Cooperation and government support to rape victims to ensure their welfare, Third, Need to be expected in daily interaction, society to not directly hostile to women who are pregnant outside of marriage.Keywords: the provision of abortion- contravention-human rights